Lumbar intervertebral disk degeneration in elite competitive swimmers: A case control study - Kaneoka, K.; Shimizu, K.; Hangai, M.; Okuwaki, T.; Mamizuka, N.; Sakane, M.; Ochiai, N. (The American Journal of Sports Medicine, 2007)
Background: The majority of orthopaedic problems experienced by competitive swimmers are related to pain in the shoulder, low back, and knee. Three of 39 national swim team members were hampered in their performance due to lumbar disk herniation at an international competition in 2001. There has been no previous research into lumbar disk degeneration in elite competitive swimmers.